INTEGRATING ENGLISH LANGUAGE INSTRUCTION IN SCIENCE EDUCATION: A COMPREHENSIVE PEDAGOGICAL APPROACH - Mahmudjanova Dilshoda Adhamjon daughter (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The integration of English language instruction into science education is pivotal for preparing students to navigate the global scientific community, where English dominates as the primary medium of communication. This article examines evidence-based methodologies Content and Language Integrated Learning (CLIL), Task-Based Learning (TBL), and Inquiry-Based Learning (IBL)-to facilitate the simultaneous development of linguistic proficiency and scientific literacy. By embedding English instruction within authentic scientific contexts, these approaches foster critical thinking, precise communication, and interdisciplinary skills. The paper explores their theoretical foundations, practical applications, and cognitive benefits, supported by examples such as designing experiments and presenting findings in English. Challenges, including varying proficiency levels and cognitive overload, are addressed through scaffolding and teacher training. The findings underscore the transformative potential of integrated pedagogies in equipping students for academic and professional success in a globalized scientific landscape.